A study of Singapore’s off-peak car (OPC) scheme the motorists' perspective - Mohamad Farhan Sukri. (2012)
The Off-Peak Car (OPC) schemes have been implemented in Singapore since 1991 and had undergone various developments. Its objective is to reduce traffic congestion during the peak hours. This study would undertake a critique of Singapore's unique OPC scheme as a Traffic Demand Management (TDM) measure. It would trace the development of the Weekend Car (WEC) scheme to the OPC and revised OPC schemes and analyse the usage patterns of the OPCs and the enforcement of its rules and regulations. Thus, leading on to examine the effectiveness of the scheme and review its current relevance in attracting motorists to own an OPC over a normal car.